TINDAKAN ULTRA VIRES ORGAN PEMERINTAHAN DAN KONSEKUENSI HUKUMNYA - Efendi, A'an; Sudarsono, Sudarsono (Faculty of Law, Universitas Diponegoro, 2024)
Article 17 paragraph (2) of the Government Administration Law which positions ultra vires as a species in the genus abuse of power is incorrect. Ultra vires is its own type of deviation from the use of power which is different from abuse of power. The legal consequences of ultra vires actions by government organs are null and void, which means that from the beginning the action and its legal consequences have no existence in law, and are not invalid as stipulated in Article 70 paragraph (1) of the Government Administration Law. Actions of government organs that are null and void must be declared in a state administrative court decision that the action is null and void and does not create or change any legal situation.